Do Female Students Learn Language Better Than Male Students? - Nurjanah, Aisyah; Situmorang, Annisa; Paturohmah, Pepi Siti; Ruminda, Ruminda (Matriks Jurnal Sosial dan Sains, 2024)
This study explores the comparative comparison of language learning capabilities between male and female students by using a qualitative-descriptive methodology. The main tool used in the study is questionnaire to investigate possible differences in how genders approach and do well in language acquisition. The goal of this research is to provide an answer regarding “do female students learn language better than male students?”. In addition to providing a more complete knowledge of potential differences of learning style, learning strategies and motivation variations across genders in their language learning experiences, the findings aim to offer critical insights into educational practices. This investigation not only improves teaching strategies but also establishes the foundation for creating inclusive and productive language learning settings.